Bilinguals from Boghazköi, II - Cooper, Jerrold S.
KВо 7 1 + KUB 37 115 and KВо 7 2; K 9235 (+) 15997; 4 R 23 No. 3 (+) DT 120 (+) K. 2368 (+) 11661 (+) 13305; 4 R 13 No. 2 + Sm. 542 + K. 4831 + 4862; STT 197; Additions and Corrections to Part I; Anhang von R. Borger (K. 9235 + 15997).